Cortical desmoids in adolescent top-level athletes. (14th May 2015) - Tscholl, Philippe M; Biedert, Roland M; Gal, Imre
Two adolescent, highly active athletes are presented with unspecific symptoms of anterior knee pain. Conventional radiographs and magnetic resonance imaging (MRI) showed a suspicious but pathognomonic cortical irregularity of the dorsal, medial femoral condyle. Cortical desmoid is one of the most common incidental osseous findings on conventional radiographs and MRI of the knee. It often needs no follow-up examination in asymptomatic patients. Malignancy needs however to be ruled out.